Integrating Ecotheology into Islamic Education: A Multicultural Perspective Study among Kindergarten Students - Mukhamad Ilyasin; Bahrani Bahrani; Sa'da Qamariah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study examines the integration of ecotheology in early childhood Islamic education through a multicultural perspective at Al-Hikmah Kindergarten, Samarinda, East Kalimantan. The study is based on the view that the ecological crisis is not only related to physical environmental damage, but also reflects a lack of ethical, spiritual, social, and cultural awareness in caring for nature. This research employs a case study qualitative design. Data were collected through classroom observations, semi-structured interviews with the principal and Islamic education (PAI/IMTAQ center) teachers, as well as documentation including lesson plans, school programs, and child development assessment formats. The observation subjects were 17 kindergarten B students aged 5–6 years. The findings show that ecotheological values””such as tauhid (oneness of God), khalifah (stewardship), amanah (trust), mizan (balance), rahmah (compassion), and cleanliness ethics””are integrated through prayers, illustrated stories, visual media, IMTAQ center activities, role modeling, habits such as handwashing, proper waste disposal, plant care, outdoor activities, and cultural practices. The school’s proximity to the Mahakam River and Kampung Ketupat provides concrete ecological and cultural learning spaces, while the students’ multicultural backgrounds strengthen cooperation, tolerance, mutual assistance, and respect for diversity. This article emphasizes that integrating ecotheology in early childhood Islamic education should be concrete, enjoyable, contextual, and inclusive, enabling children to recognize nature as God’s creation, care for the environment, use resources wisely, and live harmoniously in a diverse society.